The transition to the euro and economic convergence of Romania - Aurel Iancu (Romanian Academy, National Institute for Economic Research, 2017)
By the Treaty of Accession to the EU, Romania opted for the euro adoption. According to the Maastricht Treaty, since 2014 Romania has fulfilled the nominal convergence criteria, thus becoming apt to adopt the euro. But a careful analysis of the reality and the lessons learnt from the Euro Area crisis show that the real convergence criterion is able to ensure the sustainability of the nominal criteria and the adequate functioning of the economy. To adopt the euro we should look for the minimum threshold of the GDP per capita calculated by the Purchasing Power Parity. In our study, we consider different real convergence thresholds on corresponding time horizons for comparison: at a 70% convergence level of Romania in relation to the EU 28 average, we need 8-9 years, and a full convergence level (100%) requires 22-26 years.
Keywords: F15; F43; F55; F59; 330; Euro adoption; catch up; nominal convergence; real convergence; exchange rate